Pembuatan Modul Ajar Peta Online untuk Masyarakat Umum - Sukadi; Noor Fitria Azzahra; Seno Aji (Universitas Merdeka Madiun, 2024)
One of the conveniences on the internet is the existence of online maps, where with online maps, if someone wants to go to an area, they no longer need to look for information by asking other people, but can use an online map called Google Maps. In this community service, a teaching module was created to create online maps with Google My Maps which is expected to help the general public who want to develop map facilities provided by the internet, in this case Google. The method of implementing this community service is planning, analysis, collecting data via the internet (which includes Longitude coordinates, Latitude coordinates, and names of tourist attractions), implementing online map making, and making reports. The data used as a sample is map data of tourist attractions in Pacitan Regency. The result of this community service is a teaching module or activity report that can be used to develop map facilities provided by the internet, in this case Google.